A complex network of regulatory elements in Ikaros and their activity during hemo-lymphopoiesis - Kaufmann, Christoph (Oxford University Press, 2003)
Regulated expression of Ikaros is critical for normal hemopoiesis and lymphocyte development. To elucidate the mechanisms underlying transcription of Ikaros, tissue-specific DNase I-hypersensitive sites (DHS) were mapped throughout the Ikaros locus, and several promoters were identified. The activity of these regulatory regions was elucidated using an enhanced green fluorescent protein (EGFP) reporter in transgenic mice. Two genomic fragments, each containing a distinct promoter and its associated DHS cluster, were found to be active in the myeloid (DHS-C2 and DHS-C3) and B-cell (DHS-C3) lineages. Although neither of these regulatory regions was active within the majority of differentiating thymocytes and mature T cells, the DHS-C3 region was active at the earliest stages (DN1–DN3) of T-cell differentiation. However, when the DHS-C3 region was combined with the downstream intronic DHS-C6 cluster, its activity was maintained and raised to higher levels at subsequent stages of T-cell differentiation. This combination of regulatory elements provided reporter expression that closely resembles that of endogenous Ikaros during hemo-lymphopoiesis, and it decreased (but did not alleviate) position effect variegation within the expressing cell types.